2019
DOI: 10.14739/2310-1210.2019.5.179431
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of association between the Pro12Ala polymorphism of PPAR-γ gene with the risk of obstetric complications

Abstract: Івано-Франківський національний медичний університет, УкраїнаМета роботи -вивчити асоціацію Pro12Ala поліморфізму гена PPAR-γ з ризиком розвитку акушерських ускладнень.Матеріали та методи. Обстежили 97 жінок із нормальною прегравідарною масою тіла, одноплідною вагітністю, терміном пологів 37 тижнів і більше та відсутністю тяжких хронічних захворювань, які були під спостереженням упродовж вагітності та 1 року після пологів. Виконали антропометрію, визначення відсотка жирової маси тіла (% ЖМТ) методом спектральн… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 1 publication
0
5
0
1
Order By: Relevance
“…On the other hand, the peroxisome proliferator-activated γ-receptor ( PPAR γ) rs1801282 SNV and its relationship with GWG were analyzed in 97 Ukrainian [ 34 ] and 162 Turkish women [ 32 ]; the authors concluded that based on adjusted models, Ala carriers had a greater probability of undergoing excessive GWG. In addition, the TT genotype from endothelial nitric oxide synthase (eNOS) Glu298Asp SNV in the Ukrainian sample was related to an increment of 5 kg compared to the other genotypes (GT and GG) [ 33 ].…”
Section: Relevant Sectionsmentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, the peroxisome proliferator-activated γ-receptor ( PPAR γ) rs1801282 SNV and its relationship with GWG were analyzed in 97 Ukrainian [ 34 ] and 162 Turkish women [ 32 ]; the authors concluded that based on adjusted models, Ala carriers had a greater probability of undergoing excessive GWG. In addition, the TT genotype from endothelial nitric oxide synthase (eNOS) Glu298Asp SNV in the Ukrainian sample was related to an increment of 5 kg compared to the other genotypes (GT and GG) [ 33 ].…”
Section: Relevant Sectionsmentioning
confidence: 99%
“…This hypothesis has been inconsistent with other studies. The effect of this SNV could be affected by race; for example, in 97 Caucasian Ukrainian women, the genetic variant of PPAR-γ Pro12Ala was associated with greater GWG and a high frequency of excessive GWG [ 34 ].…”
Section: Relevant Sectionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Основні етіологічні чинники надмірного блювання вагітних залишаються невідомими, проте попередні дослідження показали роль генетичних факторів і факторів зовнішнього середовища, що сприяють реалізації генетичної схильності [7,3]. Існує однозначна думка, що ХГЛ є важливим регулятором диференціації трофобластів і міграції клітин ворсинчастого цитотрофобласта в стінки спіральних артерій плацентарного ложа для створення прямого контакту між хоріоном плода й материнським кровотоком.…”
Section: / том XXVII /unclassified